Carbon ink for high-speed printing
By using the conductive composition composed of resin, graphite and charcoal black, the problem of insufficient conductivity and functional losses in high -speed printing in high -speed printing is solved, and an efficient and low -cost conductive ink is applied to high -speed printing.
Patent Information
- Application Number
- CN202180034194.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-14
- Filing Date
- 2021-04-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-04-20
Smart Images

Figure BDA0003933347060000101 
Figure BDA0003933347060000111 
Figure BDA0003933347060000121
Abstract
Description
Technical Field
[0001] The present invention relates to conductive compositions that can be used in high-speed printing techniques such as flexography and rotogravure printing. Background Art
[0002] Conventional conductive inks have been applied to substrates, for example, by screen printing, rotary screen printing, and dispensing. These printing methods are considered to be relatively slow printing methods.
[0003] For example, screen printing is a traditional printing method that has been used extensively in the printed electronics industry. Screen printing produces solid layers with a thickness of 5 to 15 microns, and the conductivity of these layers is sufficient to carry current for a large number of applications. The printing speed of screen printing is about 3 to 20 m / min.
[0004] These mature high-speed printing technologies are also used in the graphic industry (e.g., manufacturing packaging). Typically, a thin layer of colored ink is applied to obtain an image on a substrate. In this method, the colors are applied as individual dots, but to the naked eye, these individual dots provide a very good colored image. For conductive applications, the dried ink must be connected to provide a stable current, and therefore conductive inks cannot be applied as individual dots.
[0005] There is a high demand for new intelligent consumer products (such as smart diapers, RFID antennas and medical electrodes). In order to be able to mass-produce these new intelligent consumer products, higher speed printing technology (such as flexographic printing and rotary gravure printing) is needed. The term "high-speed printing" means a speed of up to and exceeding 200m / min in this article. The ink used in these new intelligent consumer products requires a certain conductivity, some of which require high conductivity, and for some, lower conductivity is sufficient. For high-demand applications, ink must have high conductivity, so silver is used as a conductive material, but for lower demand applications, lower resistance levels are sufficient, so carbon or graphite can be used as conductive materials. However, not all conductive inks are suitable for high-speed printing methods. In fact, most of the currently available conductive inks are not suitable for high-speed printing methods.
[0006] One of the recent trends in the printed electronics industry is the search for higher speed printing methods that are cost effective. It has been found that currently available conductive inks containing carbon are not suitable for high speed printing. The main reasons for the failure of current carbon inks are that they are not conductive enough when printed in thin layers and that after they are applied, the dried coating often retains too much solvent. Another reason for failure is that current carbon inks lose their functionality when printed at high speeds.
[0007] Therefore, there is a need for conductive inks which can be applied by high-speed printing methods while maintaining good technical properties and which are cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1a and Figure 1b Illustration of flexographic printing trials on an industrial printing press.
[0009] Figure 2 Illustrated is a microscopic image of the dry coating after rotogravure printing of Example 3 with backlighting (magnification 25X).
[0010] Figure 3 Illustrated is a microscopic image (magnification 25X) of the dry coating after rotogravure printing of Example 7 with backlighting. Summary of the invention
[0011] The present invention relates to a conductive composition, which comprises: a) a resin selected from nitrocellulose, chlorinated polyester, chlorinated polyether, chlorinated polyvinyl, chlorinated polyacetate and a mixture thereof; b) conductive particles, which comprise graphite and carbon black, wherein the ratio of the graphite to the carbon black is 1:1 to 5:1; and c) a solvent, wherein the ratio of the conductive particles to the resin is 0.20:1 to 4:1.
[0012] The present invention includes a conductive film comprising the conductive composition according to the present invention.
[0013] The invention relates to the use of the conductive composition according to the invention in flexographic or rotogravure printing.
[0014] The present invention comprises the use of the conductive composition or conductive film according to the present invention in smart personal hygiene products, heating elements, pressure sensors, smart books, smart labels and shielding applications. DETAILED DESCRIPTION
[0015] The present invention is described in more detail in the following paragraphs. Unless explicitly stated otherwise, each aspect described in this way can be combined with any other one or more aspects. In particular, any feature that is indicated as being preferred or advantageous can be combined with any other one or more features that are indicated as being preferred or advantageous.
[0016] In the context of the present invention, unless the context indicates otherwise, the terms used should be interpreted according to the following definitions.
[0017] As used herein, the singular forms "a" and "an" and "the" include both singular and plural referents unless the context clearly dictates otherwise.
[0018] As used herein, the terms "comprising," "comprises," and "comprised of" are synonymous with "including" and "includes" or "containing" and are inclusive or open-ended and do not exclude additional, unrecited members, elements, or method steps.
[0019] Recitations of numerical endpoints include all numbers and fractions subsumed within the corresponding ranges, as well as the recited endpoints.
[0020] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned herein are based on weight.
[0021] When an amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper value and a preferred lower value, it should be understood that any range obtained by combining any upper value or preferred value with any lower value or preferred value is explicitly disclosed, regardless of whether the obtained range is explicitly mentioned in the context.
[0022] All references cited in this specification are hereby incorporated by reference in their entirety.
[0023] Unless otherwise defined, all terms (including technical and scientific terms) used in the present invention have the meanings commonly understood by ordinary technicians in the field to which the present invention belongs. By way of further guidance, term definitions are included to better understand the teachings of the present invention.
[0024] The applicant has investigated conductive inks applied by high speed printing methods. In particular, the sheet resistance of layers (of various thicknesses) of conductive ink applied by a gravure printer was investigated and it was found that a low sheet resistance (in Ohm / sq / 25 μm) does not always provide the lowest resistance in a thin layer. In this case, the thin layer is considered to have a thickness of 1 to 2 μm. In further experiments, it was found that the low sheet resistance can be optimized by selecting an ideal combination of resin and conductive particles. A further advantage of the ideal combination of resin and conductive particles is that an ink with suitable viscosity, a good value for money and good conductivity in a thin layer can be provided.
[0025] The present invention relates to a conductive composition, which comprises: a) a resin selected from nitrocellulose, chlorinated polyester, chlorinated polyether, chlorinated polyvinyl, chlorinated polyacetate and a mixture thereof; b) conductive particles, which comprise graphite and carbon black, wherein the ratio of the graphite to the carbon black is 1:1 to 5:1; and c) a solvent, wherein the ratio of the conductive particles to the resin is 0.20:1 to 4:1.
[0026] The conductive composition according to the invention has a combination of conductive particles which are optimized to provide good conductivity in thin layers. Furthermore, the solvent and rheology make it possible to print the composition at high speed and to dry the composition (after dilution).
[0027] The conductive composition according to the present invention comprises a resin. Suitable resins for use in the present invention are selected from nitrocellulose, chlorinated polyesters, chlorinated polyethers, chlorinated polyvinyls, chlorinated polyacetates and mixtures thereof, and the resin is preferably nitrocellulose.
[0028] The term chlorinated polyvinyl herein means vinyl chloride polymers (homopolymers) and / or vinyl chloride copolymers containing 2, 3, 4 or more comonomers.
[0029] The term chlorinated polyester is used herein to refer to copolymers of vinyl chloride and copolymerizable polyester oligomers.
[0030] The term chlorinated polyether refers herein to copolymers of vinyl chloride and copolymerizable polyether oligomers.
[0031] The term chlorinated polyacetate is used herein to refer to copolymers of vinyl chloride and vinyl acetate.
[0032] Preferably, the chlorinated polyethylene is selected from vinyl chloride polymers; vinyl chloride vinyl acetate copolymers; vinyl chloride vinyl stearate copolymers; vinyl chloride 1,2-dichloroethylene copolymers; vinyl chloride (meth) acrylonitrile copolymers; vinyl chloride methyl (meth) acrylate copolymers; vinyl chloride butyl (meth) acrylate copolymers; vinyl chloride dicarboxylic acid copolymers; vinyl chloride fumaric acid copolymers; vinyl chloride maleic acid copolymers; vinyl chloride dibutyl fumarate copolymers; vinyl chloride diethyl maleate copolymers; terpolymers of vinyl chloride, vinyl acetate and dicarboxylic acid; terpolymers of vinyl chloride-vinyl acetate-vinyl alcohol; and mixtures thereof.
[0033] Preferably, the chlorinated polyester is selected from copolymers of vinyl chloride and polyester acrylate oligomers.
[0034] Preferably, the chlorinated polyether is selected from copolymers of vinyl chloride and polyether acrylate oligomers such as dipropylene glycol diacrylate.
[0035] Preferably, the chlorinated polyacetate is a copolymer of vinyl chloride and vinyl acetate.
[0036] The selected resins release solvents easily, which makes the composition suitable for consumer use. In addition, these resins are preferred because they provide low resistance and high conductivity. Generally, these resins fully disperse the conductive particles.
[0037] In a highly preferred embodiment, nitrocellulose is used as the resin. Nitrocellulose is particularly preferred because it provides excellent conductivity while it dissolves well and releases the solvent used quickly.
[0038] In another highly preferred embodiment, a vinyl chloride-vinyl acetate-vinyl alcohol terpolymer is used as the resin.
[0039] Suitable commercially available resins for use in the present invention include, but are not limited to, Solbin A from ShinEtsu and NC-E560 IPA 30% from Dow.
[0040] The resin may be present in the conductive composition according to the present invention in an amount of 2 to 25 wt%, preferably 3 to 23 wt%, more preferably 4 to 21 wt%, based on the total weight of the composition.
[0041] When the amount of resin exceeds 25%, the viscosity of the composition increases to a level where the composition is no longer printable at high speeds, while too low an amount (less than 2%) results in poor coating, low viscosity, and settling of the resin and conductive particles.
[0042] The conductive composition according to the present invention comprises conductive particles, wherein the conductive particles comprise graphite and carbon black, wherein the ratio of the graphite to the carbon black is 1:1 to 5:1.
[0043] Applicants have found that good results can be achieved by using a combination of graphite and carbon black as the conductive particles.
[0044] The particle size D90 of suitable graphite for the present invention is preferably 1 μm to 75 μm, more preferably 2 μm to 45 μm, more preferably 3 μm to 25 μm, even more preferably 3 μm to 10 μm. The particle size is measured by laser diffraction. In this method, a laser beam illuminates a cell containing a graphite sample suspended in water, and the resulting diffraction pattern is collected by the system and analyzed using light scattering developed by Mie. The particle size distribution is calculated and the amount for 90% is reported.
[0045] In addition to the particle size D90, or as an alternative feature of suitable graphites for use in the present invention, preferably 0.25 μm 2 / g to 25m 2 / g, more preferably 4m 2 / g to 22m 2 / g, more preferably 7m 2 / g to 21m 2 / g specific surface area, where the specific surface area is measured by BET nitrogen adsorption. The measurement is carried out by measuring the adsorption-desorption isotherm of nitrogen on the surface of the material with the help of the Brunauer-Emmet-Teller algorithm; a certain amount (accuracy 0.01 mg) of powder is weighed in a sample tube. Subsequently, the sample undergoes a series of heating and cooling processes from the evolution of the pressure in the sample tube, and the amount of nitrogen adsorbed during the different steps is calculated; the specific surface area is calculated from the data and is expressed in m 2 Reported in units of / g.
[0046] In a preferred embodiment, the graphite has a particle size D90 of 1 μm to 75 μm, preferably 2 μm to 45 μm, more preferably 3 μm to 25 μm, even more preferably 3 μm to 10 μm; and / or 0.25 μm 2 / g to 25m 2 / g, preferably 4m 2 / g to 22m 2 / g, more preferably 7m 2 / g to 21m 2 / g of specific surface area; wherein the particle size is measured by laser diffraction, and wherein the specific surface area is measured by BET nitrogen adsorption.
[0047] The preferred specific surface area and particle size of the graphite provide low electrical resistance and good electrical conductivity in thin layers, as individual features or as a combination, and good printability.
[0048] Typically, too large a graphite particle size results in a lower specific surface area and, in addition, can make it difficult to release the particles from the cell during the printing process. However, too small a graphite particle size can be too expensive to produce and have a larger specific surface area, which results in a higher viscosity. High viscosity is not ideal for high-speed printing and requires a lot of dilution before application, which can adversely affect the conductivity of the printed layer.
[0049] Less than 0.25m 2 / g of graphite surface area will lead to a decrease in conductivity, while higher than 25m 2 A specific surface area of less than 100 μg / g may cause problems with the viscosity of the composition and is furthermore not a cost-effective component.
[0050] Suitable commercially available graphites for use in the present invention include, but are not limited to, Timrex SFG6 from TIMCAL Graphite & Carbon.
[0051] The oil absorption value of suitable carbon black for use in the present invention is preferably 70 ml / 100 g to 500 ml / 100 g, more preferably 100 ml / 100 g to 300 ml / 100 g, more preferably 150 ml / 100 g to 200 ml / 100 g, wherein the oil absorption value is measured according to ASTM D2414.
[0052] In addition to the oil absorption value, or as an alternative feature, suitable carbon blacks for use in the present invention preferably have a specific surface area of 30 m 2 / g to 1400m 2 / g, more preferably 100m 2 / g to 700m 2 / g, more preferably 150m 2 / g to 350m 2 / g, wherein the specific surface area is measured according to BET. This method is based on the record of nitrogen adsorption at 77K. According to the model proposed by Brewer, Emmett and Teller (BET), the monolayer capacity can be determined. Based on the cross-sectional area of the nitrogen molecule, the monolayer capacity and the sample weight, the specific surface area can be calculated.
[0053] In a preferred embodiment, the carbon black has an oil absorption value of 70 ml / 100 g to 500 ml / 100 g, preferably 100 ml / 100 g to 300 ml / 100 g, more preferably 150 ml / 100 g to 200 ml / 100 g; and / or 30 ml / 100 g. 2 / g to 1400m 2 / g, preferably 100m 2 / g to 700m 2 / g, more preferably 150m 2 / g to 350m 2 The specific surface area of 200 Å / g is 200 Å / g, wherein the oil absorption value is measured according to ASTM D2414, and wherein the specific surface area is measured according to BET.
[0054] Preferred specific surface area and oil absorption values alone or in combination provide good printability and low electrical resistance in thin layers.
[0055] When the oil absorption value of carbon black is too low, it means less branched carbon black and thus fewer contact points in the thin layer, which will adversely affect conductivity, while too high oil absorption value of carbon black (mainly greater than 500) will cause difficulties in the printing process.
[0056] When the specific surface area size of carbon black is too small (mainly less than 30), this may result in poor conductivity, whereas an excessively high specific surface area of carbon black (mainly exceeding 1400) may result in difficulties during printing.
[0057] Suitable commercially available carbon blacks for use in the present invention include, but are not limited to, Vulcan XC72 from Cabot and Ensaco 250G from Imerys.
[0058] According to the present invention, the ratio of the graphite to the carbon black is 1:1 to 5:1, preferably 2:1 to 4:1, and the ratio of the graphite to the carbon black is more preferably 3:1.
[0059] Applicants have found that these ratios of graphite to carbon black provide the composition according to the invention with an ideal viscosity and conductivity. It has been found that too high a concentration of carbon black relative to graphite results in a thicker printed layer. Furthermore, if the amount of carbon black is too high, the viscosity of the composition increases too high and the composition is no longer printable at high speeds.
[0060] The conductive particles may be present in the conductive composition according to the present invention in an amount of 3 to 45 wt%, preferably 4 to 43 wt%, more preferably 4.75 to 41 wt%, based on the total weight of the composition.
[0061] When the amount of the conductive particles is too low (mainly less than 3%), the amount does not provide the desired conductivity, while too high an amount (mainly exceeding 45%) may result in difficulty in handling the composition during printing.
[0062] The applicant has found that particularly good properties are obtained and the composition can be used for high speed printing when the ratio of the conductive particles to the resin is from 0.20:1 to 4:1, preferably from 0.25:1 to 3:1.
[0063] Applicants have found that this ratio of conductive particles to resin provides good viscosity and good conductivity.
[0064] The conductive composition according to the present invention comprises a solvent. The composition may comprise one solvent or a mixture of two or more solvents. Preferably, the solvent has a relatively low boiling point, preferably below 119°C, more preferably a boiling point of 80°C to 105°C. Solvents with relatively low boiling points are preferred because they dry quickly and achieve fast printing speeds.
[0065] In a preferred embodiment, the solvent is selected from toluene, ethanol, isopropanol, n-propanol, ethyl acetate, n-propyl acetate, isopropyl acetate, methyl ethyl ketone, methyl isobutyl ketone, water and mixtures thereof, preferably the solvent is selected from ethyl acetate, isopropyl acetate, n-propyl acetate and mixtures thereof, more preferably selected from isopropanol, n-propyl acetate and mixtures thereof.
[0066] These solvents are preferred because they dissolve the resin well and are easily released during the drying process.
[0067] Suitable commercially available solvents for use in the present invention include, but are not limited to, ethyl acetate from Eastman and butyl acetate from Eastman.
[0068] The solvent may be present in the conductive composition according to the present invention in an amount of 40 to 92 wt %, preferably 45 to 91 wt %, more preferably 46 to 90 wt %, based on the total weight of the composition.
[0069] If the amount of solvent is less than 40%, the viscosity of the composition may increase too high and thus adversely affect the printing properties of the composition, while higher amounts (over 90%) may adversely affect the conductivity of the composition.
[0070] The conductive composition according to the present invention is preferably prepared by the pebble mill process. In the pebble mill process, the conductive particles, resin and solvent are ground by gravel in a large mill for about 15 hours.
[0071] In one aspect of the present invention, a conductive film including the conductive composition according to the present invention may be formed.
[0072] The conductive film according to the present invention has one or more layers, wherein the thickness of each layer is 0.5 μm to 3 μm, preferably 0.75 μm to 2 μm, more preferably 1 μm to 1.5 μm.
[0073] Thin layers are desirable due to cost-effectiveness aspects, but are also desirable from a process perspective. Thinner layers mean less material build-up in the rollers used in the printing process, and this way improves print quality.
[0074] The conductive composition according to the present invention can be used for high-speed printing (such as flexographic printing or rotogravure printing).
[0075] During flexographic printing, the ink is transferred from a metal cylinder (containing tiny cells filled with ink) to a polymer sleeve (holding an image, like a stamp), and then the sleeve transfers the ink (stamp) to the substrate. The process is rapid, and the ink used must have a low viscosity to allow the process. Applying the ink using flexographic or rotogravure printing produces a dry thin layer with a thickness in the range of about 1 micron.
[0076] The conductive composition according to the invention can be printed at speeds up to and exceeding 200 m / min.
[0077] The viscosity of the conductive composition according to the invention is preferably 600 to 5000 mPas, preferably 650 to 3000 mPas, more preferably 700 to 2000 mPas, wherein the viscosity is measured by Brookfield (DV-I Prime), spindle No. 2 at 20 at room temperature.
[0078] The Applicant has found that this viscosity range is ideal for a production process for producing the conductive composition according to the invention and that furthermore this viscosity range prevents sedimentation of the composition during storage.
[0079] For flexographic or rotogravure printing, the viscosity of the composition needs to be relatively low for good release from the cell. Therefore, in a preferred embodiment, the composition according to the invention is diluted before application. Therefore, the present invention also relates to a diluted conductive composition, wherein the conductive composition according to the invention is diluted in the range of 20 to 70 wt. %, preferably 40 to 50 wt. %.
[0080] The preferred dilution range is about 40-50% by weight, and this leads to viscosities in the range of 100 mPa.s. Despite the low viscosity, the diluted composition according to the invention provides good conductivity in thin layers.
[0081] Suitable solvents for dilution are the solvents used in the compositions according to the invention. In a highly preferred embodiment, the solvent used for dilution is n-propyl acetate.
[0082] The composition according to the invention does not lose its functionality when printed at high speeds.
[0083] The present invention comprises the use of the conductive composition or conductive film according to the present invention in smart personal hygiene products, heating elements, pressure sensors, smart books, smart labels and shielding applications.
[0084] Smart personal hygiene products are for example smart diapers / absorbent articles.
[0085] Example
[0086] Table 1
[0087]
[0088] The viscosity of the composition was about 200 mPa.s.
[0089] The samples were applied to the substrate with a bar coater and dried in air. Prior to application, the samples were diluted to a solids content of 23%. The results are combined in Table 2. Example 1 provided the lowest resistance in a thick and dense layer.
[0090] Table 2
[0091] Ink Comparative Example Example 1 Example 2 Dry film thickness (μm) 16 14 13 Track resistance 1(Ohm) 274 108 208 With resistor 2(Ohm) 293 95 189 Average R(Ohm) 283.5 101.5 198.5 Ohm / sq / 25μm 18.1 5.7 10.3
[0092] The examples from Table 1 and Table 2 were applied with a 90 μm applicator.
[0093] The coating was then dried in air and the thickness of the layer was measured by using a Mitutoyo digital thickness gauge.
[0094] The film was allowed to sit for 15 minutes, a 10 x 1 cm track was separated and the resistance of the track was measured. Resistance measurements were done using a digital Keithley electrometer using a 4 point probe.
[0095] After measuring the resistance, the sheet resistance was calculated according to the following equation.
[0096]
[0097] R = Sheet resistance (in Ohm / square area / 25μm)
[0098] R(tr) = resistance of the belt (in Ohms)
[0099] H(tr) = coating thickness (in μm)
[0100] N(tr) = number of square areas
[0101] 25 = standard coating thickness.
[0102] The results are listed in Table 3. Example 2 provided the lowest resistance. The lower the thickness, the better the formulation of Example 2 compared to the other inks.
[0103] Table 3
[0104] Ink Thickness(μm) Comparative Example Example 1 Example 2 Air dried kOhm / sq kOhm / sq kOhm / sq Maximum volume ~2.4 2.2 1.1 0.7 Medium volume ~2.0 6.4 2.9 1.2 Minimum volume ~1.8 9.7 7.1 2.4
[0105] Figure 1a and Figure 1b The diagram illustrates a flexographic printing test on an industrial printing press. Both Example 1 and Example 2 were printed on PET under the same conditions by using a gravure proofer. After printing, the resistance on a strip of 50×2 mm (=25 square area) was measured and the kOhm / sq was calculated.
[0106] Example 2 provided the lowest resistance (Example 1 6.3 kOhm / sq and Example 2 2.0 kOhm / sq).
[0107] Table 4 below illustrates alternative compositions.
[0108] Table 4
[0109]
[0110] The samples were diluted until the solids content was 16%. Subsequently, Examples 3-7 were applied to the substrate using a gravure printer and dried in air. The results are combined in Table 5.
[0111] Table 5
[0112] Ink Example 3 Example 4 Example 5 Example 6 Example 7 R kOhm / sq 2.0 1.0 17.5 1.3 1.2 Ohm / sq / 25μm 17.5 16.6 26.5 17.2 30.5
[0113] Figure 2 and Figure 3 Example 3 (illustrated in FIG. Figure 2 ) and Example 7 ( Figure 3 ) of a dry coating after rotogravure printing with backlighting (magnification 25×).
[0114] The viscosity of Examples 3-5 is about 200 mPa.s. Example 7 has a higher viscosity and is not suitable for high speed printing due to the high viscosity. This is illustrated in Figure 3 In the process, the film formed is not a uniform layer but a film full of pinholes, which is not a desired feature.
Claims
1. A conductive composition, comprising: a) a resin selected from the group consisting of nitrocellulose; chlorinated polyesters; chlorinated polyethers; vinyl chloride polymers; vinyl chloride vinyl acetate copolymers; vinyl chloride vinyl stearate copolymers; vinyl chloride 1,2-dichloroethylene copolymers; vinyl chloride (meth) acrylonitrile copolymers; vinyl chloride (meth) acrylate methyl copolymers; vinyl chloride (meth) acrylate butyl copolymers; vinyl chloride dicarboxylic acid copolymers; vinyl chloride fumaric acid copolymers; vinyl chloride maleic acid copolymers; vinyl chloride dibutyl fumarate copolymers; vinyl chloride diethyl maleate copolymers; terpolymers of vinyl chloride, vinyl acetate and dicarboxylic acid; and mixtures thereof; b) conductive particles, the conductive particles comprising graphite and carbon black, wherein the ratio of the graphite to the carbon black is 1:1 to 5:1; and c) a solvent having a boiling point below 119° C., The ratio of the conductive particles to the resin is 0.20:1 to 4:
1.
2. The conductive composition according to claim 1, wherein the resin is nitrocellulose.
3. The conductive composition according to claim 1 or 2, wherein the resin is present in an amount of 2 to 25 wt% based on the total weight of the composition.
4. The conductive composition of claim 3, wherein the resin is present in an amount of 3 to 23 wt% based on the total weight of the composition.
5. The conductive composition of claim 4, wherein the resin is present in an amount of 4 to 21 wt% based on the total weight of the composition.
6. The conductive composition according to claim 1 or 2, wherein the graphite has a particle size D90 of 1 μm to 75 μm; and / or 0.25m 2 / g to 25m 2 / g specific surface area; wherein the particle size is measured by laser diffraction, and wherein the specific surface area is measured by BET nitrogen adsorption. 7 . The conductive composition according to claim 6 , wherein the graphite has a particle size D90 of 2 μm to 45 μm. 8 . The conductive composition according to claim 7 , wherein the graphite has a particle size D90 of 3 μm to 25 μm. 9 . The conductive composition according to claim 8 , wherein the graphite has a particle size D90 of 3 μm to 10 μm.
10. The conductive composition according to claim 6, wherein the graphite has a 4 m 2 / g to 22m 2 / g specific surface area.
11. The conductive composition according to claim 10, wherein the graphite has a 7m 2 / g to 21m 2 / g specific surface area.
12. The conductive composition according to claim 1 or 2, wherein the carbon black has an oil absorption value of 70 ml / 100 g to 500 ml / 100 g; and / or 30m 2 / g to 1400m 2 / g specific surface area; wherein the oil absorption value is measured according to ASTM D2414, and wherein the specific surface area is measured according to BET. 13 . The conductive composition according to claim 12 , wherein the carbon black has an oil absorption value of 100 ml / 100 g to 300 ml / 100 g. 14 . The conductive composition according to claim 13 , wherein the carbon black has an oil absorption value of 150 ml / 100 g to 200 ml / 100 g.
15. The conductive composition according to claim 12, wherein the carbon black has a 100 m 2 / g to 700m 2 / g specific surface area.
16. The conductive composition according to claim 15, wherein the carbon black has a 2 / g to 350m 2 / g specific surface area.
17. The conductive composition according to claim 1 or 2, wherein the ratio of the graphite to the carbon black is 2:1 to 4:
1.
18. The conductive composition of claim 17, wherein the ratio of the graphite to the carbon black is 3:
1.
19. The conductive composition of claim 1 or 2, wherein the conductive particles are present in an amount of 3 to 45 wt% based on the total weight of the composition.
20. The conductive composition of claim 19, wherein the conductive particles are present in 4 to 43 weight percent of the total weight of the composition.
21. The conductive composition of claim 20, wherein the conductive particles are present in 4.75 to 41 weight percent of the total weight of the composition.
22. The conductive composition of claim 1 or 2, wherein the ratio of the conductive particles to the resin is 0.25:1 to 3:
1.
23. The conductive composition according to claim 1 or 2, wherein the solvent is selected from the group consisting of toluene, ethanol, isopropanol, n-propanol, ethyl acetate, n-propyl acetate, isopropyl acetate, methyl ethyl ketone, methyl isobutyl ketone, water and mixtures thereof.
24. The conductive composition of claim 23, wherein the solvent is selected from the group consisting of ethyl acetate, isopropyl alcohol, n-propyl acetate, and mixtures thereof.
25. The conductive composition of claim 24, wherein the solvent is selected from the group consisting of isopropyl alcohol, n-propyl acetate, and mixtures thereof.
26. The conductive composition of claim 1 or 2, wherein the solvent is present in 40 to 92 weight % of the total weight of the composition.
27. The conductive composition of claim 26, wherein the solvent is present in 45 to 91 wt% of the total weight of the composition.
28. The conductive composition of claim 27, wherein the solvent is present in 46 to 90 weight percent of the total weight of the composition.
29. The conductive composition according to claim 1 or 2, wherein the viscosity of the composition is 600 to 5000 mPas, wherein the viscosity is measured by Brookfield (DV-I Prime), spindle No. 2 at 20 at room temperature.
30. The conductive composition of claim 29, wherein the composition has a viscosity of 650 to 3000 mPas.
31. The conductive composition of claim 30, wherein the composition has a viscosity of 700 to 2000 mPas.
32. A diluted conductive composition, wherein the conductive composition according to any one of claims 1 to 31 is diluted in the range of 20 to 70 wt%.
33. The diluted conductive composition according to claim 32, wherein the conductive composition according to any one of claims 1 to 31 is diluted in the range of 40 to 50 wt%.
34. A conductive film comprising the conductive composition according to any one of claims 1 to 31.
35. A conductive film according to claim 34, wherein the film has one or more layers, and wherein the thickness of the layers is from 0.5 μm to 3 μm.
36. A conductive film according to claim 35, wherein the layer has a thickness of 0.75 μm to 2 μm.
37. A conductive film according to claim 36, wherein the layer has a thickness of 1 to 1.5 μm.
38. Use of the conductive composition according to any one of claims 1 to 31 or the diluted composition according to claim 32 in flexographic printing or rotogravure printing.
39. Use of the conductive composition according to any one of claims 1 to 31 or the conductive film according to any one of claims 34 to 37 in smart personal hygiene products, heating elements, pressure sensors, smart books, smart labels and shielding applications.
Citation Information
Patent Citations
Ink composition and method for use thereof in the manufacturing of electrochemical sensors
US20050096409A1